2007
DOI: 10.1136/bjo.2006.113902
|View full text |Cite
|
Sign up to set email alerts
|

Non-responders to bevacizumab (Avastin) therapy of choroidal neovascular lesions

Abstract: Aims: To determine the characteristics of ''non-responders'' to intravitreal bevacizumab treatment in choroidal neovascularisation (CNV). Methods: Forty-three patients with visual loss due to neovascular age-related macular disease (ARMD) (44 eyes) underwent intravitreal injections of 1.25 mg (0.05 ml) bevacizumab and were followed up every 4 weeks for 2, 3 or 6 months. Re-injection was performed when persistent leakage of the CNV was determined by fluorescein angiography and retinal oedema was assessed by opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
108
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(115 citation statements)
references
References 14 publications
2
108
0
5
Order By: Relevance
“…However, despite the effectiveness of anti-VEGF therapies in most patients with AMD, there may still remain indications for MR surgery in some, such as in patients with large subretinal haemorrhages 20 or in Anti-VEGF non-responders. 21 In this respect, the results of the MARAN study will help to refine patient selection and expectations from MR surgery. …”
Section: Discussionmentioning
confidence: 99%
“…However, despite the effectiveness of anti-VEGF therapies in most patients with AMD, there may still remain indications for MR surgery in some, such as in patients with large subretinal haemorrhages 20 or in Anti-VEGF non-responders. 21 In this respect, the results of the MARAN study will help to refine patient selection and expectations from MR surgery. …”
Section: Discussionmentioning
confidence: 99%
“…Though studies comparing PDT and anti-VEGF therapy show the greater efficacy of anti-VEGF therapy 19 , there are still a number of patients who do not respond to anti-VEGF therapy 20 . These patients could potentially benefit from PDT in combination with other treatment options than anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients cannot respond to the treatment as expected. In recent studies, it has been showed that the incidence for non responsiveness to bevacizumab in treatment naïve n-AMD ranges between approximately 40 and 50% while as the percent of non responsiveness to ranibizumab was between approximately 10-20% [6][7][8][9]. Although there is currently no more evidence in the literature, a recent report demonstrated that the rates of non responsiveness to aflibercept in the treatment of n AMD based on best corrected visual acuity (BVCA) and fundus findings were approximately 8% and 13%, respectively [10].…”
Section: Editorialmentioning
confidence: 99%
“…In the light of the recent reports, it can be considered that the potential risk factors for non-responsiveness to anti-VEGF agent in the treatment of n-AMD are an initial lesion with subfoveal fibrosis or atrophy in retina pigment epithelium and photoreceptors, lesion in large size, type 1 choroidal neovascularization, serous pigment epithelium detachment (PED), haemorrhagic PED, fibrovascular PED, polypoidal choroidal vasculopathy, foveal scarring and vitreomacular traction, outer retinal tubulation, cystoid degeneration in outer retina, genetic disposition or an anti-VEGF resistance [Table 1, 13-22]. Table 1: The possible risk factors for non-responsiveness to anti-VEGF agents in the patients with nAMD [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation